Coarazuphium bambui (Carabidae: Zuphiini), a new cave-dwelling beetle from the threatened region of Serra do Ramalho, Brazil - Pellegrini, Thais Giovannini; Bichuette, Maria Elina; Vieira, Letícia (Zootaxa, 2022)
To date, 20 species of obligate cave-dwelling beetles are known from Brazil, and 12 belong to the Coarazuphium genus. In this paper, we describe Coarazuphium bambui sp. n., from two specimens, one male and one female, collected in the Gruna Boca da Lapa cave located in the municipality of Feira da Mata (Bahia state, Brazil). The most striking difference between C. bambui and other species of the genus is the presence of three pairs of fixed setae posteriorly on the head, combined with the slightly elytral sinuosity. We also provide an updated key for species identification of the Coarazuphium genus. Finally, we highlight the importance of the Serra do Ramalho karst area for the conservation of troglobite diversity in the Brazilian context.